The Students Perception toward the Teachers Teaching Method at the Tenth and Eleventh Grades of Pesantren Modern Datok Sulaiman Palopo - Wahibah Wahibah (Institut Agama Islam Negeri Palopo, 2015)
The objective of this research as to find out the students perception toward the teachers teaching method at the tenth and eleventh grades of Pesantren Modern Datok Sulaiman Palopo.